Depression Levels and Coping Strategies Among Adolescent Drug Users at Rumah Orbit Surabaya, Indonesia: A Mini Report - Lestari, Yufi Aris; Hambali, IM; Atmoko, Adi; Eva, Nur (KONSELOR, 2023)
This brief investigation checks into how depression levels and ways of dealing with problems are related among teenage drug users who are getting help at Rumah Orbit Surabaya, a drug rehab centre in Indonesia. The study used a correlational analytic approach and looked at 32 teenage drug users: 10 were admitted for inpatient care and 22 were getting therapy outside of school. The requirements for inclusion are that the teens must be involved in rehabilitation and have good social skills. Teenagers who are already drug-free are not eligible. The Beck Depression Inventory questionnaire and the Ways of Coping Checklist were used to gather data. The results show a clear connection between the subjects' coping strategies and how depressed they were. Findings show that teens who use drugs are more likely to use unhealthy ways to deal with their problems when they are depressed. In particular, most of them showed signs of borderline sadness, and a big chunk of them used unhealthy ways to deal with their problems. On the other hand, people with moderate depression were more likely to use adaptive coping techniques. This study adds to our knowledge of how sadness affects how teenage drug users deal with stress in a rehabilitation setting. Recommendations include interventions that are targeted to the severity of sadness to help people in this vulnerable group get better at therapy and coping. In the future, researchers could look into longitudinal effects and intervention methods that are better suited to people with different levels of depression in similar situations.